PENGEMBANGAN E-MODUL BERBASIS LEARNING CYCLE 7E PADA MATERI LARUTAN PENYANGGA - Yunike br Tarigan; Hermansyah Amir; Sura Menda Ginting (University of Bengkulu, 2022)
This study aims to test the feasibility of using the developed e-module, and determine student responses after using the e-module.This type of research is research and development using the ADDIE development model. The instruments used in this study wereinterviews with chemistry teachers, validation sheets, and student response questionnaires. This research was conducted at SMAN04 Bengkulu City with a research sample of 30 students of class XII IPA 2. From the result of the research obtained the feasibilitylevel of e-module based on Learning Cycle 7E on the media aspect of 93.75% while the material aspect was 80.40%. Ifaccumulated, the average percentage of the feasibility level of the developed e-module is 87.075%. Based on the results of thevalidation by the e-module validator, the developed module is “very feasible”. Based on the results of student responses to thedeveloped e-module, it was obtained a percentage of 85.20% which was included in the “very good” category. The results of thisstudy indicate that E-module Based on Learning Cycle 7E on Materials Buffer solution is very feasible to use and very feasible tobe applied in the learning process.